ANALYSIS OF THE POSSIBILITY OF USING BIOCHAR IN ASPHALT CONCRETE - Krayushkina, Kateryna; Bondarchuk, Vadym (Theory and practice of design, 2025)
Purpose. The purpose of this study is to investigate the impact of biochar, derived from various types of plant biomass, on the physical and mechanical properties of asphalt concrete mixtures. The goal is to enhance the ecological sustainability and operational performance of pavement materials in road construction. Methodology. The study involved a comparative analysis of the properties of biochar produced by pyrolysis of different biomass sources. Laboratory samples of asphalt mixtures were prepared with partial replacement of mineral filler by biochar (up to 50% by weight). These samples underwent a series of physical, chemical, and mechanical tests to evaluate their strength, moisture resistance, temperature sensitivity, and adhesion properties. Results. The findings demonstrate that adding biochar in the range of 40–50% by weight of the mineral filler improves asphalt mixture strength, reduces water saturation, enhances resistance to thermal aging, and lowers the mixture’s placement temperature – resulting in energy savings. The integration of biochar leads to a more environmentally friendly and durable pavement structure. Scientific novelty. This research systematizes, for the first time, the relationship between biochar characteristics (particle size, biomass type, moisture content) and asphalt concrete performance. It provides scientific justification for the partial replacement of conventional mineral filler with biochar without compromising the technical properties of asphalt mixtures. Practical relevance. The results can be implemented in the development of eco-efficient road surfaces with improved durability, moisture resistance, and aging stability. Additionally, this approach contributes to carbon footprint reduction and the effective utilization of organic waste in construction practices.